Central nervous system lymphoma presenting as trigeminal neuralgia: A diagnostic challenge. Issue 7 (July 2015) - Ang, Jensen W.J.; Khanna, Arjun; Walcott, Brian P.; Kahle, Kristopher T.; Eskandar, Emad N.
Abstract We describe an atypical man with diffuse large B cell lymphoma localized to the sphenoid wing and adjacent cavernous sinus, initially presenting with isolated ipsilateral facial pain mimicking trigeminal neuralgia due to invasion of Meckel's cave but subsequently progressing to intra-axial extension and having synchronous features of systemic lymphoma. Primary central nervous system lymphoma is uncommon, accounting for approximately 2% of all primary intracranial tumors, but its incidence has been steadily increasing in some groups [1]. It usually arises in the periventricular cerebral white matter, and reports of lymphoma in extra-axial regions are rare [2]. This man highlights the importance of maintaining lymphoma in the differential diagnosis of tumors of the skull base presenting with trigeminal neuralgia-like symptoms.